AB0895 Serum biomarkers to predict clinical response in proof-of-concept trials in spondyloarthritis. (23rd January 2014) - Turina, M.; Yeremenko, N.; Paramarta, J.; Vandooren, B.; Tak, P.P.; De Rijcke, L.; Baeten, D.
Abstract : Background: With TNF-blockers availability for spondyloarthritis (SpA), evaluation of new drugs requires quick ``go/no go" signals in small scale, short term proof-of-concept (PoC) trials. Biomarkers complementing clinical evaluations may help reducing length and size of these PoCs. Objectives: We aimed to identify and validate serum biomarkers to predict clinical response at group level in these trials. Methods: Matrix metalloproteinase-3 (MMP-3), Pentraxin-3 (PTX-3), high sensitive C-reactive protein (hs-CRP), calprotectin, Interleukin-6 (IL-6), Vascular Endothelial Growth Factor (VEGF), and alpha-2-macroglobulin (alpha-2-MG) were selected as biomarkers [1-3]. Serum levels were determined by ELISA in healthy controls (n=20) and at week 0 and 2 in SpA patients treated with infliximab (5 mg/kg; week 0, 2, and 6) (n=18) or placebo (n=19). Patient and physician global assessment of disease activity and BASDAI were evaluated at week 0 and 12. Results: Baseline clinical parameters were similar in both SpA cohorts, whereas treatment with infliximab but not with placebo induced significant decrease in all clinical parameters at week 12 after treatment initiation (p<0.005). Analysis of baseline serum samples revealed similar levels of selected biomarkers in the two SpA cohorts. Comparing to healthy controls, however, levels of PTX-3 (p<0.001), hs-CRP (p<0.001), calprotectin (p<0.001) and VEGF (p<0.001) were significantly increased in SpA whereas IL-6 and alpha-2-MG were not elevated. In the placebo group, levels of these biomarkers remained stable over 2 weeks. In contrast, infliximab induced a significant decrease of hs-CRP (p<0.0001), calprotectin (p<0.001), and IL-6 (p=0.04) with a similar trend for MMP-3 (p=0.063). VEGF and alpha-2-MG levels were not significantly modulated. The Standardized Response Mean (SRM), reflecting the ability to detect changes over time at the group level, was high for calprotectin (SRM 1.259) and good for hs-CRP (SRM 0.746) and MMP-3 (SRM 0.521). The SRM was low for the other biomarkers in the treated group and for all biomarkers in the placebo group. In contrast to findings at group level, linear regression to determine biomarker values at individual level revealed some significant but low correlations of changes in hs-CRP (r 2 between 0.24 and 0.36) and calprotectin (r 2 between 0.08 and 0.19) at week 2 with clinical outcome parameters at week 12. Conclusions: Early changes in serum calprotectin, hs-CRP, and MMP-3 showed a good ability to predict longer term clinical response in SpA atgroup level. These biomarkers are currently being validated in independent PoCs. References: De Rycke L, Baeten D, Foell D, Kruithof E, Veys EM, Roth J et al.: Differential expression and response to anti-TNFalpha treatment of infiltrating versus resident tissue macrophage subsets in autoimmune arthritis. J Pathol 2005, 206: 17-27. Kruithof E, De Rycke L, Vandooren B, De Keyser F, FitzGerald O, McInnes I et al.: Identification of synovial biomarkers of response to experimental treatment in early-phase clinical trials in spondylarthritis. Arthritis Rheum 2006, 54: 1795-1804. Vandooren B, Kruithof E, Yu DT, Rihl M, Gu J, De Rycke L et al.: Involvement of matrix metalloproteinases and their inhibitors in peripheral synovitis and down-regulation by tumor necrosis factor alpha blockade in spondylarthropathy. Arthritis Rheum 2004, 50: 2942-2953. Disclosure of Interest: None Declared